Determination of Key Business Processes and Strategies to achieve Sustainable Sharia Spa - Deta Indriana; Achmad Firdaus; Yono Haryono (Universitas Darussalam Gontor, 2023)
In Indonesia, Muslim women are beginning to seek out spas that adhere to sharia law. However, it is not supported by sufficient research. How are the key business processes of sharia spas and what are the strategies to achieve sustainable sharia spas. Performance maslahah approach (MaP) which consists of six aspects, namely worship orientation, internal process orientation, talent orientation, learning orientation, customer, and property orientation. Data were obtained through literature studies, observations andin-depth interviews with experts, academics and spa practitioners in Indonesia. Data were analysed by NVIVO. The key business processes of Sharia Spa are determined in each organization's benefit orientation. Each key business has success indicators. Strategies are determined to meet these indicators. Indicators of worship orientation are praying before working for dhikr while serving, social programs for the community and stakeholder commitment. Internal process orientation indicators are the use of raw materials and processes, spa facilities and services and employment. Indicators of talent orientation are spa certification competence and spiritual competence. Indicators of learning orientation are competency-based training in the field of spa and spa organization learning. Indicators of customer orientation are customer satisfaction and customer complaint handling. Asset orientation indicators are the management of spa operational costs, spa revenue streams and zakat payments. The strategy to achieve a sustainable sharia spa is determined by considering three main factors, namely the business, owner and operator, and environmental factors.